INTEGRATING ISLAMIC COUNSELING INTO PAI INSTRUCTION TO ENHANCE CHARACTER AND LEARNING QUALITY: A CASE STUDY - Ahmad Pirdaus; Siti Juariah (CV. TOTUS TUUS, 2026)
The persistent challenge in Islamic Religious Education (PAI) in many Indonesian schools is that learning often remains cognitively oriented, while the internalization of Islamic values into students’ daily self-regulation and behavior is uneven; this issue is particularly salient in vocational schools where integrity, discipline, and workplace ethics are essential. This study aimed to analyze how Islamic Guidance and Counseling (BK Islam) is implemented to improve the quality of PAI learning at SMK Negeri 2 Setu, with specific attention to BK–PAI collaboration and student outcomes across Bloom’s cognitive, affective, and psychomotor domains. Using a qualitative case study design, data were collected through observations of religious routines and counseling practices, semi-structured interviews with BK and PAI teachers, documentation review, and student perspectives (n = 30) via questionnaire and confirmatory interviews; the data were analyzed thematically and mapped onto Bloom’s domains. The findings indicate that Islamic elements are present in BK services (e.g., occasional use of Qur’anic verses/hadith and akhlaq–ibadah guidance), yet integration remains incidental and not institutionalized through standardized modules, indicators, or systematic documentation. BK–PAI collaboration is visible through joint programs (e.g., pesantren kilat, keputrian, daily kultum, congregational prayers, and Jumat Berkah), but it is not consistently managed as an integrated planning–implementation–evaluation cycle. Student-perceived benefits are strongest in affective and behavioral routines (worship awareness, self-control, respectful conduct), while higher-order cognitive gains (analyzing–evaluating–creating) appear limited; major barriers include time constraints, limited resources, and weak reporting practices, alongside students’ strong demand for contextual and digital support channels. The study concludes that BK Islam at SMKN 2 Setu constitutes a promising practice rather than a validated model, and it should be strengthened through institutional SOPs, shared BK–PAI indicators, periodic evaluation routines, and ethically protected digital counseling options. Future research should employ multi-site and mixed-method designs, incorporate longitudinal tracking, and test digital-enhanced BK–PAI integration models with clearer outcome measures and implementation fidelity indicators.